A Novel External Nasal Splint. Issue 1 (March 2019) - Honeybrook, Adam; Woodard, Charles R.; Simmons, Walter N.
Every year, hundreds of thousands of individuals suffer from nasal bone fractures, and in 2016, more than 780 000 rhinoplasty surgeries were performed globally. As part of the comprehensive care for these patients, external nasal splints are routinely used during the healing process. Nasal splints stabilize the bony and cartilaginous nasal framework and provide compression to the nose, thereby reducing nasal edema and hastening recovery. In this article, we present a novel external nasal splint that addresses some of the shortcomings of other commercially available nasal splints.